Reverse wedge osteotomy for Madelung's deformity in a high school student: A case report. (September 2021) - Tajika, Tsuyoshi; Kuboi, Takuro; Endo, Fumitaka; Hatori, Yuhei; Chikuda, Hirotaka
Madelung deformity is a congenital disorder with the malformation of anterior ulnar bowing of radius and a dorsally protruding ulnar head caused by premature growth disturbance at the medial volar aspect of the distal radius. This report describes a bilateral idiopathic Madelung deformity in a 17-year-old woman treated successfully using reverse wedge osteotomy of the distal radius in a symptomatic left wrist. Reverse wedge osteotomy can orient the radial joint surface while correcting the whole radius length by reversely putting the wedge bone removed from the distal metaphysis of radius, the base of which is cut from the surplus of the radial and dorsal cortical bone in the hypotrophic portion. We corrected the palmar subluxation of the carpus, restored her good function, and relieved her wrist pain.